Does choice of antiretroviral drugs matter for inflammation?. Issue 5 (4th May 2019) - Gutierrez, María del Mar; Mateo, María Gracia; Vidal, Francesc; Domingo, Pere
ABSTRACT: Introduction : The massive implementation of combination antiretroviral therapy (cART) has forever changed the landscape of HIV infection. This unprecedented success has turned HIV infection into a manageable chronic disease. The increased survival of people living with HIV is, however, shadowed by a high burden of aging-related comorbidities. The pathogenic basis underlying this excess of co-morbid conditions is most likely a persistent inflammatory and immune activation state, despite an optimal control of HIV replication, which in turn has largely been attributed to bacterial or bacterial products translocation from the gut. Area covered : This review is focused on the relationship between cART and the chronic inflammatory and immune activation status in otherwise virologically well-controlled people living with HIV (PLWH). Particular focus will be placed on the differences, if any, between distinct cART modalities, with emphasis on less-drug cART regimens, and especially on dual therapies. Expert opinion : Research to address the increased inflammatory and immune activation status of cART-treated, HIV-infected patients, should focus on adjuvant means of therapy, rather than on the cART regime itself. With current antiretrovirals, no difference between dual and triple regimens has been demonstrated, provided that virological and immunological outcomes be non-inferior.